Changes In Gait, Balance and Comfort That Is Felt in The Use of Shoes with Height-Elevating Insole with A Height Of 5, 7 and 9 Cm - Christopher Lawrence; Chrismis Novalinda; Linda Chiuman; Ermi Girsang (International Journal of Health and Pharmaceutical (IJHP), 2022)
The Use of shoes with height-elevating insole lately has been rife in the community. Use sol high this can affect the function of static and dynamic body, where physical changes in the body. As a result, generate a posture which is not stable, not balanced, and less comfortable when used in daily activities. Have many kinds of shoes with high soles with distinctions high pedestal the soles of shoes that allow the existence of different effects for the body. Objective, Prove the change of gait, balance and comfort in use of the shoe with a height-elevating the insole at the height of 5, 7, 9 cm. Material and Methods, experimental Research with pre and post test design. Subjects are men aged 20-22 years with a Body Mass Index (BMI) normal. Thirty people who are willing to follow the study and meet the inclusion and exclusion criteria were divided randomly into 3 groups, group a 5 cm, 7 cm and 9 cm, which respectively amounted to 10 people. Each group performed a walk test to test gait, one leg stands and tandemstand to test the balance with the barefoot/barefoot, shoes with height- elevating the insole with the same high. Results, the Results of this study show a change in gait and balance that are significant between barefoot and wearing shoes high soles (p=0.005). But the difference between the shoes with the height-elevating insole with a height of 5, 7 and 9 cm is not significant on the parameters of gait (p=0.329) but there is a change of balance in between shoes high soles 5, 7, 9 cm on the parameters of the balance (p=0.000). Conclusion, there are differences in the balance and there was no difference in gait on the use of the shoe’s height-elevating insole different (5, 7, 9 cm).